1996
DOI: 10.1021/cm9504697
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Hexagonally Packed Mesoporous Tantalum Oxide Molecular Sieves

Abstract: The synthesis and characterization of Ta-TMS1, a new member of a growing family of hexagonally packed transition-metal oxide mesoporous molecular sieves (termed TMS1) is described. Ta-TMS1 exhibits a hexagonal array of pores which can be varied in size from 20 to 40 Å and surface areas of over 500 m2/g. The thermal and hydrothermal stabilities of Ta-TMS1 are 500 and 450 °C, respectively, making this system the most stable transition-metal oxide molecular sieve yet isolated. The high hydrocarbon adsorption capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
194
0
7

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(208 citation statements)
references
References 34 publications
7
194
0
7
Order By: Relevance
“…A similar formation mechanism was observed in the case of tantalum. 27 However, the covalent bond can only be formed upon evaporation of ethanol after the combination of amine and tantalum. In case of titania and amines, 28 it was shown that no initial covalent bond could be formed between the amine and the titania source and the amine is more likely hydrogen-bonded.…”
Section: Results and Discussion A Strategies Toward Zirconia Hybridsmentioning
confidence: 99%
“…A similar formation mechanism was observed in the case of tantalum. 27 However, the covalent bond can only be formed upon evaporation of ethanol after the combination of amine and tantalum. In case of titania and amines, 28 it was shown that no initial covalent bond could be formed between the amine and the titania source and the amine is more likely hydrogen-bonded.…”
Section: Results and Discussion A Strategies Toward Zirconia Hybridsmentioning
confidence: 99%
“…Five signals are observed, which can be assigned chemical reactivity of each component. The hydrolysis ratio as follows: (H ϭ H 2 O/M), the use of a catalyst [8] , of complexing li-δ ϭ 800Ϫ650 µ 2 O oxo-bridges gands [11] , or of a templating medium [12] [13] are the main δ ϭ 600Ϫ450 µ 3 O oxo-bridges factors that must be mastered by the sol-gel chemist in or-δ ϭ 400Ϫ300 µ 4 O oxo-bridges der to achieve this control.…”
Section: Introductionmentioning
confidence: 99%
“…Such syntheses are open to air with various aging times and environmental conditions that can influence the porosity of these materials. Most studies of mesoporous transition metal oxide (MTMO) materials have focused on groups I-IV, including Y, Ti, Hf, Zr, V, Nb, Ta, Cr, Mo and W 6,7,[11][12][13][14][15][16] . Sol-gel chemistry of these transition metals (TMs) can be controlled in alcoholic solutions with proper acidity adjustments, and such metals interact strongly with polyethylene oxide (PEO) groups of non-ionic surfactants by accepting electron density to their empty d-orbitals 17 .…”
mentioning
confidence: 99%